Efek Literasi Digital dan Pengembangan Kapasitas terhadap Keberhasilan UMKM di Kota Makassar - Badar, Muhammad; Normiyati, Normiyati; Hajrah, Hajrah (Movere Journal, 2025)
This study aims to analyze the influence of digital literacy and capacity building on the success of Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. In facing the challenges of the digital era, digital literacy and capacity building are important factors that determine the sustainability and competitiveness of MSMEs. This study uses a quantitative approach with a survey of 125 MSME actors selected by proportional stratified random sampling. The data were analyzed using the Partial Least Squares (PLS) method to test the relationship between independent and dependent variables. The results of the study show that digital literacy has a positive and significant influence on the success of MSMEs. Digital literacy helps MSMEs improve operational efficiency, expand markets, and create innovations in business processes. In addition, capacity building shows a more dominant influence on the success of MSMEs. Capacity building includes improving managerial skills, resource management, and product innovation, which strengthens the internal capabilities of MSMEs to cope with changes in the business environment. The findings of this study confirm that digital literacy and capacity building complement each other in supporting the success of MSMEs. Digital literacy allows access to technology and market opportunities, while capacity building ensures the internal ability of MSMEs to manage and utilize technology effectively. The combination of these two factors provides a strong foundation for the sustainability of MSMEs in the midst of increasingly complex business dynamics.